If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(s + -10) = -173 Reorder the terms: 10(-10 + s) = -173 (-10 * 10 + s * 10) = -173 (-100 + 10s) = -173 Solving -100 + 10s = -173 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '100' to each side of the equation. -100 + 100 + 10s = -173 + 100 Combine like terms: -100 + 100 = 0 0 + 10s = -173 + 100 10s = -173 + 100 Combine like terms: -173 + 100 = -73 10s = -73 Divide each side by '10'. s = -7.3 Simplifying s = -7.3
| 4y^3+y^2=0 | | x+(x+250)=1280 | | 7(4s+1)=175 | | 4(2l+1)=60 | | x^2=36/169 | | -10m+-5=95 | | (1/2-x)2 | | 190=3x^2-2 | | 3x-7=-15x+35 | | 4x-16+12=0 | | 4z+1=2z+7 | | 5x+2(5x-4)=18 | | Cos(35)=2/x | | 4.50=(2x)^2/(0.15-x) | | 0=16t^2+88t | | g(x+1)=5-3(x+1) | | h(x)=2 | | 4x-2=4(x-5) | | 144x^2-36=(12x+6)(12x-6) | | 4cos^2(x)+4sin^2(x)=0 | | tx^2+3x-14=0 | | x-3.1x=14.7+12 | | x-4.8=9 | | 7x+9x+7x=274 | | 4a+5-7= | | 14+2x=180 | | 0=-16t^2+44t-24 | | 14x+7x+9x=137 | | -3(2+5b)= | | 76(-2-3)=19x+6 | | 7-12(x+3)=13-15(2x-5) | | 0=-16t^2+20t+36 |